Da água ao viaduto: a transmigração da Festa do Espírito Santo na Casa dos Açores de São Paulo e a permanência da memória - Henyei Neto, Gyorgy (2013)
The following dissertation presents symbolic ressignifcation of a cultural/religious manifestation within the immigration movement from the Azores to São Paulo. The hypotheses reflect on the observation of the several possibilities for re-adaptation of a religious ceremony, such as the Holy Ghost Festival, in a new place, which, even though it has some resemblances on their origins, are both original constructions of the human creativity. The House of the Azores in São Paulo was the object of ethnographical research, been part also of the thematic on the diversity among the other House of the Azores in Brazil and around the world. During the three-chapter work, there would be shown the methods and questions to be answered, in the hope of enlarge the knowledge about the Azorean immigration to Brazil and also offer a renewed look inside the glossary of interpretation of significance trauma-suffered significance, as a transposition from one side to the other of the Atlantic. The point reached is that the materiality and the immateriality are not stationary inferences in the universe, but always substance and product of human invention